Analisis Prosedur Penyelesaian Kredit Bermasalah pada Koperasi Pegawai Wilayah Mandiri (Kopegwil Medan) - Nurul Deswita Maharani; M.Ikhsan Harahap (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research focuses on the procedure for resolving problematic credit in the Mandiri Medan employee cooperative. This research was carried out at the Karya Bersama Sejahtera Cooperative using the Qualitative Descriptive Analysis method which has primary and secondary data sources through interviews and documentation. The research subject is the Mandiri Regional Employees Cooperative, and the research object is bad credit and its resolution. The research results show (1) The causes of bad credit at the Mandiri Medan Regional Employees Cooperative are internal and external factors. Internal factors, namely: lack of selectivity on the part of the cooperative in analyzing credit provision, bad faith on the part of the employees of the Mandiri Medan Regional Employee Cooperative, and a weak credit monitoring system. External factors, namely: a decline in economic conditions, bad faith from debtors, and the consequences of natural disasters. (2) The impact of bad credit on the Mandirir Medan Regional Employees Cooperative is reducing cooperative income, cash flow becomes stagnant, cooperative capital decreases, and customer confidence decreases. (3) Efforts made to overcome bad credit at the Mandiri Medan Regional Employees Cooperative are rescheduling, restructuring, confiscation of collateral and credit write-off.